1993
DOI: 10.1111/j.1439-037x.1993.tb01080.x
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of the Cumulation of Iron, Copper and Sodium During Development to Maturity of Soybean Seed

Abstract: The dynamics of the cumulation of iron, copper and sodium with four genotypes of soybean cultivated in the same topographical and agrotechnical conditions during three years was followed. Sampling was done in weekly intervals until complete maturity of seed. It was found out that the most intense cumulation took place during the seed development stages III and IV at the time of mostly expressed metabolic activity of the seed. The absolute values of the contents were increasing along with seed maturing and maxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…According to other authors no uniform tendency has been recorded in the accumulation of potassium [38,39], calcium [36,40], magnesium [36,38], iron [36,38,41], or phosphorus [28,38,40]. Slipcevic et al [42] observed that the accumulation of mineral compounds is modified by air temperature, being also to a great degree affected by the metabolic activity of seeds.…”
Section: Mineral Componentsmentioning
confidence: 96%
“…According to other authors no uniform tendency has been recorded in the accumulation of potassium [38,39], calcium [36,40], magnesium [36,38], iron [36,38,41], or phosphorus [28,38,40]. Slipcevic et al [42] observed that the accumulation of mineral compounds is modified by air temperature, being also to a great degree affected by the metabolic activity of seeds.…”
Section: Mineral Componentsmentioning
confidence: 96%
“…Karlen et al (1982) found that irrigation changed the accumulation and distribution of several mineral nutrients in the vegetative and pod tissues of soybean plants. Final mineral concentration in soybean seed was affected by climatic conditions and precipitation during seed development (Parker et al 1981;Slipcevic et al 1993). Prolonged wet weather during the preharvest period damaged soybean and increased the concentrations of phospholipids and iron in finished oils (Robertson et al 1973;Evans et al 1974;List et al 1977).…”
Section: Mots Clés: Soja Glycine Max Composition Minérale Températurementioning
confidence: 99%
“…Iron defi ciency, such as that which occurs with excessive NO 3 -1 , may induce diff erent changes in gene expression among genotypes (Blair et al, 2010). Although the degree of expression of seed micronutrient concentrations may vary with environments, superior mineral content selected at one location is usually stable across years and other sites or treatments (Slipcevic et al, 1993;Spehar, 1994;Beebe et al, 2000;Welch and Graham, 2004). Shen et al (2002) concluded that high seed Fe levels improved chlorosis resistance in wheat and that genotypic seed Fe levels were an aspect of genotypic diff erences in resistance to Fe defi ciency.…”
Section: Methodsmentioning
confidence: 99%